High incidence and prevalence of MS in Møre and Romsdal County, Norway, 1950–2018. Issue 3 (May 2020) - Willumsen, Johannes Sverre; Aarseth, Jan Harald; Myhr, Kjell-Morten; Midgard, Rune
Abstract : Objective: To determine prevalence and longitudinal trends in incidence of MS in Møre and Romsdal County, Western Norway, from 1950 to 2018. Methods: Retrospective longitudinal population-based observational study. All patients diagnosed, or living, with MS in Møre and Romsdal were identified as incident or prevalent cases from local, regional, and national sources. We compiled the data in the Norwegian Multiple Sclerosis Registry and Biobank and used the aggregated data set to calculate incidence and prevalence rates using population measures obtained from Statistics Norway. Results: On January 1, 2018, the estimated prevalence was 335.8 (95% CI, 314.1–358.5) per 100, 000 inhabitants, with a female:male ratio of 2.3. From 1950 through 2017, we observed a considerable ( p < 0.001) increase in average annual incidence rates from 2.1 (95% CI, 1.3–3.3) to 14.4 (95% CI, 11.9–17.3) per 100, 000. From 2005 through 2017, the incidence among women increased from 17.1 (95% CI, 14.0–20.7) to 23.2 (95% CI, 18.7–28.5) per 100, 000, whereas the incidence among men declined from 10.3 (95% CI, 7.9–13.2) to 5.9 (95% CI, 3.4–8.8) per 100, 000. Conclusion: Møre and Romsdal County in Western Norway has the highest prevalence of MS reported in Norway. The incidence has steadily increased since 1950, and during the latest 15 years, we observed opposing trends in sex-specific incidence rates.